Evaluating and managing the sustainability of investments in green and sustainable chemistry: An overview of sustainable finance approaches and tools - YILAN, GÜLŞAH (My University, 2022)
Green chemistry (GC) was developed to maximise resource efficiency and minimise hazards in chemical processes and products. Over time, the approach evolved into green and sustainable chemistry (GSC), which aims at promoting the development of an ecologically friendly society. GSC encourages society\"s reliance on sustainable materials and technologies/processes and supports the ambitious sustainability targets set by international organisations. It also steers public attention to the provision of sustainable solutions for producers, consumers and investors. Since GSC implementation requires significant financial investment, this paper describes a broad range of approaches and tools to assess the sustainability of potential investments and shows, although with a primary focus on environmental sustainability, how life cycle approaches could be used to define enhanced key performance indicators. Thus, the paper may serve as a useful reference for: (i) chemical companies interested in evaluating the sustainability performance of activities requiring financial investment, and (ii) investors interested in evaluating the sustainability of potential financial investments.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences